Hypoxia-Inducible Factor-1α (HIF-1α) Potentiates β-Cell Survival after Islet Transplantation of Human and Mouse Islets. Issue 2 (February 2013) - Stokes, Rebecca A.; Cheng, Kim; Deters, Natasha; Lau, Sue Mei; Hawthorne, Wayne J.; O'connell, Philip J.; Stolp, Jessica; Grey, Shane; Loudovaris, Thomas; Kay, Thomas W.; Thomas, Helen E.; Gonzalez, Frank J.; et al.
A high proportion of β-cells die within days of islet transplantation. Reports suggest that induction of hypoxia-inducible factor-1α (HIF-1α) predicts adverse transplant outcomes. We hypothesized that this was a compensatory response and that HIF-1α protects β-cells during transplantation. Transplants were performed using human islets or murine β-cell-specific HIF-1α-null (β-HIF-1α-null) islets with or without treatment with deferoxamine (DFO) to increase HIF-1α. β-HIF-1α-null transplants had poor outcomes, demonstrating that lack of HIF-1α impaired transplant efficiency. Increasing HIF-1α improved outcomes for mouse and human islets. No effect was seen in β-HIF-1α-null islets. The mechanism was decreased apoptosis, resulting in increased β-cell mass posttransplantation. These findings show that HIF-1α is a protective factor and is required for successful islet transplant outcomes. Iron chelation with DFO markedly improved transplant success in a HIF-1α-dependent manner, thus demonstrating the mechanism of action. DFO, approved for human use, may have a therapeutic role in the setting of human islet transplantation.